Bending Properties of Elephant Grass Fiber Reinforced Epoxy Resin Composites - Nurhayati, Alwiyah (Fakultas Ilmu Tarbiyah dan Keguruan, UIN Walisongo, 2015)
The use of composite materials with natural fiber filler is known in the industry regarding to improvements in technology process and economic factor. The elephant grass is one of natural fiber that has a pretty good prospect, where grass-processing as filler composite materials are still not widely performed. This study aims to determine the mechanical properties that is bending properties of elephant grass fiber-reinforced epoxy polymer composite by varying its fillerâs volume fraction. The fiberÂ treated by immersing in water for 3 days. Hand lay up process used to prepare the composite specimens with 1%,Â 3% and 5% volume fraction. The dimensions of the specimens used to carry out the test adapted from ASTM D 3379-75 for Bend testing. The results showed that filler volume fraction has effect to its bending strength. Specimen with 1% filler volume fraction has the highest bending stress whereas 5% filler volume fraction specimen has the highest elasticity modulus value.